Fuzzy logic system and mediation device node with grids for energy saving in wireless sensor network - Salameh, Emad Mohammed Ibbini (2019)
Wireless Sensor Networks (WSN) are widely used in many applications. However, it still suffering from many issues such as packet loss, idle listening, high delay, and distance between nodes which all contribute to increase energy consumption and dissipation in WSN. In order to reduce this energy dissipation, this research concentrates on the Hierarchal routing Medium Access Control (MAC) protocols on how to solve the aforementioned problems. This research proposes the Grid Mediation Device (GMD) Node to minimize the idle listening of the active dura- tion for each node, the nodes are put to sleep mode for a reasonably long period of time and they wake up for a short time only to receive data. This behavior reduces the energy consumption for each sensor while minimizing the delay since the clusterheads will not wait for the sleeping nodes that have no data to send. Thereafter, the active clusterheads will be also put in the sleeping mode once they finish their data transmission. Simulation and mathematical model of the proposed GMD protocol have confirmed that the proposed GMD can improve the lifetime for all sensor nodes in the network, due to minimizing the idle listening time for each node. Moreover, adding Multi-levels of grids and Multi-level of MD node to the GMD protocol that will minimize the distance of sending data from each level cluster grid to another level until reach to the base station instead of sending data directly from any cluster to the base station, because the path between nodes and cluster head is not reliable and the nodes are far from each other in different grid. This research leads to reduce packets lost problem as well makes the network more reliable which is another contribution of this study. Lastly, this research adding Fuzzy logic system to the grids to minimize the problem of the distance between nodes as using three fuzzy logic criteria for each node will lead to choosing the optimal location and energy for each clusterhead and each node. The three pro- posed protocols have been compared to the Two-Dimensional Technique Based on Centre of Gravity and Energy (TDTCGE) protocol which is used two-dimensional technical centers (energy Centres and Gravity Centres) that will help to reduce the energy consumption and distances between nodes. Moreover, some of the proposed protocol derives better system performance such as end-to-end delay, throughput, lifetime, and energy saving. The Grid Mediation Device (GMD) protocol with Mathematical model has improved the lifetime around 88% as compared with the TDTCGE. In addition, The Fuzzy Logic grids (FLG) protocol saves more than 8% energy battery by adding the Fuzzy logic with the three criteria’s (Distance between nodes, distance to the basestation, residual energy) that will minimize the radius competitions between nodes and the clusterhead, and between the nodes and BS by 52% more than TDTCGE protocol. GMD Simulation protocol de- creases the mean of delay by 40% because of the sleeping mode, and which node has data that it has the turn to transmit data only. In addition, Multilevel GMD Proposed protocol reduces the packets lost by 65%. This Research Work improves the lifetime and saving more energy which is also more reliable and efficiency for the wireless sensor network.